Legal rights of Chinese Muslims in the case of Conversion to Islam in Malaysia: with reference to family law issues - Abdul Hak, Nora; Mohd Zin, Najibah; Mahmud, Mek Wok (2018)
This paper focuses on the issues of conversion of one of the party to a non- Muslim marriage to Islam. In Malaysia, there are some legal problems that need to be addressed particularly concerning the rights of a wife to the ancillary claims after the dissolution of the marriage such as maintenance, division of matrimonial property and custody of children. These issues have been discussed by the Malaysian courts in their judgments when they preside over cases involving conversion to Islam. Among the issues that have been raised is whether a non-Muslim wife is entitled to maintenance when her husband converted to Islam and if she is still entitled the next question is for how long will she get the maintenance. Other issues discussed in the paper are; which party that shall be entitled to the custody of the child and also issue concerning the legal status of the marriage. The paper analyses the legal provisions including the recent amendment to the Law Reform (Marriage and Divorce) Act 1976. It also examines court cases, which involve Chinese parties on conversion to Islam.